การศึกษาการส่งมอบงานก่อสร้างในประเทศไทย : ปัญหาและแนวทางแก้ไข - ธราดล สุธีรภัทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
To study the handing-over processes in Thailand in order to identify causes of the problems existing during the processes and suggest the solution guidelines. The research is conducted by interviewing owners, construction management teams, and contractors who involve in the handing-over processes to collect information regarding the handing-over procedures, the responsibility of each party, the required documents and the problems encountered both during handing-over and during utilizing the buildings. The frequency of the problems is analyzed to classify the main causes of the problems. There are two types of handing-over processes found in the researched projects: one step and two steps. The similarity these two types is that the documents will be handed over only after the construction part is completed while the difference lies in the rights and responsibilities of the owners and the contractors. The research identifies that the causes of the problems occurred in two periods: 1) during the construction period and 2) during the handing-over period. The two main causes in the first period are the document management where the necessary data are not properly updated and the ineffective construction time management. The two main causes in the latter period are the inspection for work completion where the acceptance criteria has not been properly set up in advance and the inadequate concern on handing-over the documents andmaterials to the owners. The details of handing-over procedures are suggested as the solution guidelines for all parties to prepare themselves before entering into the handing-over processes in construction projects